Exploring Students’ Learning Motivation Orientation in the Algorithms and Computer Programming Course (A Case Study of Information Technology Education at UMTAS) - Sulidar Fitri; Novi Nurjanah; Dinda Budi Utami; Lutfiah Syifa Nur Kamila; Taufik Nur Wahid Shafari (Journal of General Education and Humanities, 2026)
The Algorithms and Computer Programming course constitutes a fundamental component of information technology education; however, it is often perceived by students as a challenging subject. This condition highlights learning motivation as a crucial factor in successful learning outcomes. This study aims to explore students’ learning motivation orientation in the Algorithms and Computer Programming course. An exploratory quantitative descriptive approach was employed, involving 23 students as respondents. Data were collected using a learning motivation questionnaire and analyzed using descriptive statistics in including frequencies and percentages. The results indicate that 95.7% of students expressed a positive attitude toward the programming course. Students’ learning motivation orientation was predominantly intrinsic (65.2%), while extrinsic motivation also played a notable role (39%). Although 61% of students perceived the course as difficult, overall learning motivation remained high. These findings suggest that students’ learning motivation orientation is adaptive and resilient. The implications of this study emphasize the importance of instructional strategies that strengthen intrinsic motivation while constructively managing extrinsic motivation.